DIGITAL TERRAIN MODELING (DTM) WITH RTK GPS FOR CERTAIN ENGINEERING USES - NIK MOHO SHUKRI, NIK MOHD F AKRUL FIDZRIE (Universiti Teknologi Petronas, 2008)
Digital terrain modeling is a process to obtain desirable models of tbe land surface. The objectives of this project are to produce a DTM witb RTK GPS as well as getting familiar with RTK GPS usage. This project covers tbe understanding on dealing with RTK GPS equipment as method for data collection to create DTM. The methodology involved preparing tbe RTK GPS, preparing tbe case study area, starting collecting data, processing tbe collected data, creating tbe terrain modeling and modeling analyzing. The DTM can be further analyzed to estimate tbe volume for cut and fill of tbe area at certain height. RTK GPS method is recommended for survey metbod straightness, consume less time for collecting data in generating DTM and suitable for all types of surveys.